A Wide-Band Millimeter-Wave On-Chip Six-Port Reflectometer - Ming-Che Lee; Hsin-Pei Yeh (Proceedings of Engineering and Technology Innovation, 2025)
Following the previous success of measuring the reflection coefficients of devices under test at 20 GHz, this paper proposes a new six-port reflectometer (SPR) chip that aims to work at 40 GHz. The new SPR is implemented with the 0.13-μm IBM BiCMOS-8HP technology, and the overall chip area is 1.5 mm in width and 1 mm in height. To demonstrate the SPR’s excellent performance over a wide band, this study utilizes a programmable tuner to create fifteen different loads for the SPR to measure at 30 GHz, 40 GHz, and 50 GHz, respectively. Among the loads, the programmable tuner serves as an important instrument for producing various sliding terminations, which are essential for calibrating the SPR. Compared with the measurement results of a vector network analyzer, the SPR displays maximum measurement errors of -28.6 dB, -32.4 dB, and -27.7 dB while operating at 30 GHz, 40 GHz, and 50 GHz.